2014
DOI: 10.1016/j.breast.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Detailed evaluation of one step nucleic acid (OSNA) molecular assay for intra-operative diagnosis of sentinel lymph node metastasis and prediction of non-sentinel nodal involvement: Experience from a London Teaching Hospital

Abstract: One step nucleic acid (OSNA) is a molecular diagnostic assay for intra-operative detection of sentinel node metastases. This study compared OSNA with standard histopathology in 283 nodes from 170 patients to evaluate sensitivity, specificity and concordance of the two methods. Additional analysis was done to investigate how cytokeratin 19 mRNA copy number affects prediction of non-sentinel node positivity. OSNA sensitivity was 93.2% and specificity 95.8%. Concordance between OSNA and histology was 95.6%. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…OSNA assay is a molecular-based intraoperative detection method for SLN metastases that has several advantages over frozen sections; it is a fast, standardized technique in which the entire lymph node is examined and provides quantitative results [2]. In this study, univariate analysis showed that tumor size, number of SLN macrometastases and CK19 mRNA copies (TTL) determined by OSNA assay were significantly associated with non-SLN metastases.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…OSNA assay is a molecular-based intraoperative detection method for SLN metastases that has several advantages over frozen sections; it is a fast, standardized technique in which the entire lymph node is examined and provides quantitative results [2]. In this study, univariate analysis showed that tumor size, number of SLN macrometastases and CK19 mRNA copies (TTL) determined by OSNA assay were significantly associated with non-SLN metastases.…”
Section: Discussionmentioning
confidence: 74%
“…Combined analysis of nine studies that compared OSNA with histopathology demonstrated high concordance between both methods (96%) and reported high sensitivity, specificity and negative predictive value for OSNA [2]. As the OSNA assay is essentially an automated procedure, it has clear advantages in standardization, reproducibility and objectivity.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, Banerjee et al . showed that mRNA copy numbers < 1400 were never associated with histologically proven metastasis in NSLN at ALND . It would be interesting to determine whether this cut‐off for mRNA copy numbers varies among different breast cancer subtypes or among tumors showing different molecular features as p53 expression.…”
Section: Discussionmentioning
confidence: 99%